Answer:
- 3log(10) -2log(5) ≈ 1.60206
- no; rules of logs apply to any base. ln(x) ≈ 2.302585×log(x)
- no; the given "property" is nonsense
Step-by-step explanation:
<h3>1.</h3>
The given expression expression can be simplified to ...
3log(10) -2log(5) = log(10^3) -log(5^2) = log(1000) -log(25)
= log(1000/25) = log(40) . . . . ≠ log(5)
≈ 1.60206
Or, it can be evaluated directly:
= 3(1) -2(0.69897) = 3 -1.39794
= 1.60206
__
<h3>2.</h3>
The properties of logarithms apply to logarithms of any base. Natural logs and common logs are related by the change of base formula ...
ln(x) = log(x)/log(e) ≈ 2.302585·log(x)
__
<h3>3.</h3>
The given "property" is nonsense. There is no simplification for the product of logs of the same base. There is no expansion for the log of a sum. The formula for the log of a power does apply:
![\log(a)\log(b)=\log(a^{\log(b)})=\log(b^{\log(a)})](https://tex.z-dn.net/?f=%5Clog%28a%29%5Clog%28b%29%3D%5Clog%28a%5E%7B%5Clog%28b%29%7D%29%3D%5Clog%28b%5E%7B%5Clog%28a%29%7D%29)
Numerical evaluation of Mr. Kim's expression would prove him wrong.
log(3)log(4) = (0.47712)(0.60206) = 0.28726
log(7) = 0.84510
0.28726 ≠ 0.84510
log(3)log(4) ≠ log(7)
55mph.
you can solve it using the equation distance=speed x time
your total distance is 714, and you have 2 trains, one traveling some speed, x, and one traveling x+8, both traveling for 7 hours.
your equation would look like this
![714 = x(7) + (x+8)(7)](https://tex.z-dn.net/?f=714%20%3D%20x%287%29%20%2B%20%28x%2B8%29%287%29)
and you can then solve for x, which would be 47. this is the speed of the slower train, but 47+8=55 with give you the speed of the faster train.
The answer to this question is 8.86666666667
Answer:
m<1 = 45°
m<2 = 76°
m<3 = 80°
Step-by-step explanation:
<u>Points to remember</u>
1). Vertically opposite angles are equal
2). Sum of angles of a triangles is 180°
<u>To find the measures of given angles</u>
From the figure we get,
m<1 = 45° [Vertically opposite angles]
By using angle sum property <2 + 59 + 45 = 180
m<2 = 180 - 104
m<2 = 76°
Also m<1 + m<3 + 55 = 180
m<3 = 180 - (m<1 + 55)
= 180 - (45 + 55)
= 180 - 100
m<3 = 80°
Step-by-step explanation:
<u>Given</u>
- f(x) = 4x³ + 3x² - 2x - 1
<u>Divide it by the following:</u>
<u>(a) 2x + 1</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ + 2x²) + (x² + 1/2x) - (5/2x + 5/4) + 1/4 =
- 2x²(2x+1) + 1/2x(2x + 1) - 5/4(2x + 1) + 1/4 =
- (2x + 1)(2x² + 1/2x - 5/4) + 1/4
Quotient = 2x² + 1/2x - 5/4
Remainder = 1/4
<u>(b) 2x - 3</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ - 6x²) + (9x² - 13.5x) + (11.5x - 17.25) + 16.25 =
- (2x -3)(2x² + 4.5x + 5.75) + 16.25
Quotient = 2x² + 4.5x + 5.75
Remainder = 16.25
<u>(c) 4x - 1</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ - x²) + (4x² - x) - (2x - 1/2) - 3/2 =
- (4x - 1)(x² + x - 1/2) - 3/2
Quotient = x² + x - 1/2
Remainder = - 3/2
<u>(d) x + 2</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ + 8x²) - (5x² + 10x) + (8x + 16) - 17 =
- (x + 2)(4x² - 5x + 8) - 17
Quotient = 4x² - 5x + 8
Remainder = - 17